Caregiver factors influencing family-based treatment for child and adolescent eating disorders: a systematic review and conceptual model - Alex McCord; Kylie Rice; Adam Rock (PeerJ)
Introduction The need to assess and manage familial factors influencing family-based treatment (FBT) has been identified in the literature in the context of improving outcomes. While some studies have attempted to address this need, results have not been unified into a framework and to date, no conceptual model exists to bring these factors together for use in clinical practice. A systematic review was conducted to fill this gap and addressed the following question: which caregiver factors influence FBT outcome for child and adolescent eating disorders? Methodology The protocol was registered in PROSPERO (CRD42022338843) and utilized the PRISMA framework. A total of 1,994 results were returned from EBSCO Host, Embase, ProQuest, PubMed Central, SCOPUS and Web of Science. Screening returned 164 studies for full-text-review with third-party replication to reduce risk of bias. Thirty-nine articles were included and organized in an evidence hierarchy including both quantitative and qualitative methodologies. Heterogeneity of the data precluded meta-analysis; results were synthesized and grouped using a systematic-narrative approach. Results Influential caregiver factors were identified and grouped into eight domains: caregiver capacity, confidence, readiness, internalizing factors, externalizing factors, food-related factors, support network and family function. Factors within each domain and their influence on treatment outcome were reported. A conceptual model, caregiver factors influencing treatment (Care-FIT) was produced as a graphical representation of the identified domains and factors by frequency of appearance. Conclusion Caregiver factors can significantly impact FBT outcome, and given the importance of their role in treatment, effective identification and management of caregiver factors is warranted. The conceptual model can be used in clinical case formulation and to support further exploration of the degree to which factors are influential. Identifying caregiver factors likely to influence treatment can facilitate support to enhance treatment and recovery.